A literature review on dyscalculia: What dyscalculia is, its characteristics, and difficulties students face in mathematics class - Resminati Dinda Salisa; Meiliasari Meiliasari (Fakultas Tarbiyah Universitas Ibrahimy, 2023)
Dyscalculia is a specific learning condition that affects the comprehension and manipulation of numerical concepts, which can impact students' academic performance and well-being in mathematics education. The research methodology used was a systematic literature review that aimed to identify and synthesize the existing evidence regarding the differences in understanding of dyscalculia, its characteristics and the difficulties that students with dyscalculia may face in class. The search string used in electronic databases, such as Crossref and Google Scholar, to generate articles for the review were “dyscalculia” and “dyscalculia characteristics.” After the study selection process and appraising its quality, 23 articles met the selection criteria and were reviewed to synthesize answers to the research questions. The findings suggest despite many differences in understanding what dyscalculia was and it was clear that dyscalculia is a specific learning condition that affected students’ comprehension and manipulation of numerical concepts. Students with dyscalculia exhibit various characteristics, the most noticeable of which was low mathematics achievement scores. The difficulties faced by students with dyscalculia in the classroom were numerous. However, the primary obstacles they faced involved comprehending and applying mathematical concepts, as these difficulties could lead to others, such as executing mathematical problem-solving instructions. Educators might comprehend the diverse characteristics of dyscalculia to provide appropriate support and accommodations for students with difficulties.